Power electronics. - Pollefliet, Jean, 1937- (Academic Press, 2018)
Power Electronics: Switches and Converters explains the principles and practices of power electronics, electronic switches and converters with the support of illustration and worked examples, guiding the reader from theory to real-life application. Covering insights on industrial applications and practical aspects of power electronic devices and power converter systems, the book is intended for engineers, researchers and students in the field of power electronics who are interested in advanced control of power converters and the exploration of new applications of control theory.